PENGARUH KUALITAS PRODUK, HARGA DAN CITRA MEREK TERHADAP KEPUASAN KONSUMEN DAN WORD OF MOUTH PERUSAHAAN CONATO DI JEMBER - Mochammad Nasirudin; Diah Yulisetiarini; Imam Suroso (STIE Mandala Jember, 2018)
This research is a confirmatory and explanatory research at three outlets of Conato bakery in Jember. The data used in this study is the primary data obtained through the distribution of questionnaires. The population in this study were all consumers of three outlets of Conato in Jember. The number of samples used 135 samples. The technique or method of sampling used is proposive random sampling. The analysis model used in this research is Structural Equation Modeling (SEM) analysis. The results of this study indicate that the brand image is the variable of the greatest influence on customer satisfaction. Consumer satisfaction significantly affects the word of mouth of consumers from outlets of Conato in Jember. Product quality, price and brand image through customer satisfaction as intervening variable can increase the influence on word of mouth. These results can be concluded that consumer satisfaction is the most important variable role in consumer behavior research in making purchases at stores Conato in Jember. Keywords: Product Quality, Price, Brand Image, Consumer Satisfaction and Word of Mouth